The Human Factor in Mergers, Acquisitions, and Transformational Change. - Rafique, Muhammad. (Studien Zum Physik- und Chemielernen Series, 2021)
Balancing theory with practice, this book looks at the financial due diligence, cultural compatibility, and emotional sensitivity at various stages of the M&A and offers a practical process model. Business leaders, change agents, coaching and mentoring practitioners will find the rare combination of great interest.